2013
DOI: 10.1186/1750-0680-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Forest production predicted from satellite image analysis for the Southeast Asia region

Abstract: BackgroundThe objective of this study was to demonstrate a new, cost-effective method to define the sustainable amounts of harvested wood products in Southeast Asian countries case studies, while avoiding degradation (net loss) of total wood carbon stocks. Satellite remote sensing from the MODIS sensor was used in the CASA (Carnegie Ames Stanford Approach) carbon cycle model to map forest production for the Southeast Asia region from 2000 to 2010. These CASA model results have been designed to be spatially det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…In Indonesia, for example, the main driving forces of forest loss in provincial areas are poorly controlled infrastructure development, mining, and conversion to crop plantations (Potter et al 2013). Although these activities are legal, they should be shifted from high productivity areas to lower productivity areas, as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Indonesia, for example, the main driving forces of forest loss in provincial areas are poorly controlled infrastructure development, mining, and conversion to crop plantations (Potter et al 2013). Although these activities are legal, they should be shifted from high productivity areas to lower productivity areas, as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we classify NPP based on Natural Breaks (Jenks optimization) applied in ArcMap. A study by Potter et al (2013) used this approach to divide NPP into low, moderate and high production forest categories in tropical forest of Southeast Asia. The method minimized the average deviation of each class, while maximizing each class's deviation from the means of the other groups (Jenks 1967).…”
Section: Quantification Of Net Primary Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The CASA model was also capable of predicting annually summed NPP with an R 2 = 0.90 on a global scale using the NOAA Advanced Very High Resolution Radiometer (AVHRR) VI and regressing against over 1900 observed NPP data points [ 22 ]. The model has been used successfully in measuring the global effects of deforestation on NPP [ 21 , 26 ], particularly in tropical Amazonian and Asian carbon fluxes [ 23 , 27 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that loggings, i.e. clear-cutting and forest degradation, can be detected as temporal changes in surface height [ 31 ],[ 32 ]. The latter studies detected the logging-induced decreases from the 90 m SRTM C-band DSM to a recent and higher resolution X-band DSM.…”
Section: Introductionmentioning
confidence: 99%